Sanksi Adat Akibat Kawin Lari pada Masyarakat Desa Pulau Raman Kecamatan Pemayung Kabupaten Batanghari - Maryati, Maryati; Indah, Sri Ayu; Rostarum, Triamy (Wajah Hukum, 2024)
Elopement is not a culture, but there has been a shift in values in the order of social life that occurred in the village of Raman Island. This was triggered by a feeling of dissatisfaction with a decision taken by the woman so that it has an impact on the continuation of the life journey towards marriage. What cannot be achieved is due to the policy of parents being more dominant in determining their children's life partners, so that children do not have the authority to decide for themselves. This is done because of the conditions that make the youth of Raman Island village take a stance which is considered an action to resolve the problems they face which they cannot afford. Resolved well, and the parents' decision regarding the child's rights in making decisions in determining his life partner was defeated by the tenacity of the principles carried out by the woman's parents, they wanted their child to be a candidate who met their expectations, such as having a job and earning an income. which is large enough, so that the child will not have a difficult life in the future. However, the journey of human life, in determining the attitude towards marriage is not easy for a woman, where the child must obey the orders of the parents, the end of all parental decisions has been This has an impact on children, ultimately children take their own stand in dealing with the problems they face. So the shortcut that women take is how they can unite in a household life and from the young man or man because the conditions set by the prospective in-laws are more material because for application capital alone the conditions demanded are very large, the market is 50 up to 75 million, this will not be possible for men because in principle they still have low incomes on average. The salary you get while working is not enough to propose to the person you love, because the opinion you get every month is sometimes not enough, how can you add to the amount of money to propose to someone's daughter. If the conditions set by the prospective bride are too high So this makes the youth of Raman Island village take a stand to find their life partner by eloping. The culture of elopement that occurs in practice is based on behavioral patterns that are based on emotions which are in principle contrary to the existing customs in the village of Raman Island.